Analysis and Design Software Evaluation Assessment Clinical Practice (PKL / PKN) in the Web-Based Program D-III and Radiotherapy Techniques Radiodiagnostic Semarang - Sri Mulyati; Gatot Murti Wibowo; Darmini Darmini (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2013)
Has done research for the analysis and design of software evaluation clinical practice assessment (PKL / PKN) WEB based on the Diploma Program Radiodiagnostic and Radiotherapy Techniques Semarang. Needs analysis has been conducted for designing software evaluation clinical practice assessment (PKL / PKN) Web-based programming using PHP and MySQL. Analyses were performed with several stages of system analysis, analysis of the weaknesses of the old system based PIECES, a new system needs analysis, feasibility analysis and design of software systems sistem.Desain done with methods for object-oriented programming (Object Oriented Programming) created using the Unified Modeling Language (UML) that is using the use case, the database and interface design. With the analysis and design of the software, will be developed (development) and monitoring and evaluation in the next stage of research.